Femtosecond X-ray spectroscopy of haem proteins. (10th February 2021) - Bacellar, Camila; Kinschel, Dominik; Cannelli, Oliviero; Sorokin, Boris; Katayama, Tetsuo; Mancini, Giulia F.; Rouxel, Jeremy R.; Obara, Yuki; Nishitani, Junichi; Ito, Hironori; Ito, Terumasa; Kurahashi, Naoya; et al.
Abstract : We discuss our recently reported femtosecond (fs) X-ray emission spectroscopy results on the ligand dissociation and recombination in nitrosylmyoglobin (MbNO) in the context of previous studies on ferrous haem proteins. Abstract : We discuss our recently reported femtosecond (fs) X-ray emission spectroscopy results on the ligand dissociation and recombination in nitrosylmyoglobin (MbNO) in the context of previous studies on ferrous haem proteins. We also present a preliminary account of femtosecond X-ray absorption studies on MbNO, pointing to the presence of more than one species formed upon photolysis.